Adult lifetime cost of hemophilia B management in the US: payer and societal perspectives from a decision analytic model. (1st January 2021) - Li, Nanxin; Sawyer, Eileen K.; Maruszczyk, Konrad; Guzauskas, Greg; Slomka, Marta T.; Burke, Tom; Martin, Antony P.; O'Hara, Jamie; Stevenson, Matt; Recht, Michael
Abstract: Aims: Hemophilia B (HB) is a rare congenital disorder characterized by bleeding-related complications which are managed by prophylactic or post-bleeding event ("on-demand") replacement of clotting factor IX (FIX). The standard of care for severe HB is life-long prophylaxis with standard half-life (SHL) or extended half-life (EHL) products given every 2–3 or 7–14 days, respectively. FIX treatment costs in the US have been investigated, but the lifetime costs of HB treatment have not been well characterized, particularly related to the impact of joint health deterioration and associated health resource utilization. We developed a decision-analytic model to explore outcomes, costs and underlying cost drivers associated with FIX treatment options over the lifetime of an adult with severe or moderately severe HB. Materials and methods: With participation from clinicians, health technology assessment specialists and patient advocates, a Markov model was constructed to estimate bleeding events and costs associated with health states including "bleed into joint", "bleed not into joint", "no bleed" and "death". Sub-models of joint health were based on 0, 1, or ≥2 areas of chronic joint damage. US third-party payer and societal perspectives were considered with a lifetime horizon; sensitivity analyses tested the robustness of primary findings. Results: Total adult lifetime costs per patient with severe and moderately severe HB were 21, 086, 607 for SHL FIX prophylaxis, 22, 987, 483 for EHL FIX prophylaxis, and 20, 971, 826 for on-demand FIX treatment. For FIX prophylaxis, the cost of FIX treatment accounts for >90% of the total HB treatment costs. Conclusions: This decision analytic model demonstrated significant economic burden associated with the current HB treatment paradigm.